PENGARUH KEWIRAUSAHAAN SOSIAL, PERTUMBUHAN UKM TERHADAP KINERJA EKONOMI LOKAL DI KOTA BANDUNG - Wawan Supriyanto (CV. Adiba Aisha Amira, 2024)
This study investigates the influence of social entrepreneurship and Small and Medium Enterprises (SMEs) growth on local economic performance in Bandung City, Indonesia. Through quantitative analysis techniques, including surveys and Structural Equation Modeling with Partial Least Squares (SEM-PLS), this study explores the relationship between social entrepreneurship, SME growth, and economic performance. The results showed a significant positive influence between social entrepreneurship and SME growth on local economic performance. In addition, SME growth mediates the relationship between social entrepreneurship and economic performance. These findings underscore the importance of fostering an ecosystem that supports social entrepreneurship and SME development for sustainable economic growth in Bandung City.